Kanban made simple : demystifying and applying Toyota's legendary manufacturing process - Gross, John M. (AMACOM, 2003)
"The Toyota Company is renowned for the quality of its products. An integral part of that quality and of the success of the company is the manufacturing process called "kanban." Simply put, it is a production methodology that applies just-in-time principles to every stage of the process, from preproduction supply flow right through to on-demand shipping." "Until now, comprehensive "how-to" information for bringing kanban to your company has been hard to find. But with Kanban Made Simple, you can bring unprecedented productivity, flexibility, and cost-efficiency to your production lines." "Authors John Gross and Ken McInnis have provided an easy-to-follow guide to using kanban in any manufacturing environment. Gross and McInnis explain the theory, how to decide if the process is right for your plant, how to form kanban teams, and how to administer the entire program for maximum results."--Jacket